2017
DOI: 10.1146/annurev-matsci-070616-124109
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Perovskite Barium Stannate with High Electron Mobility and Thermal Stability

Abstract: Transparent conducting oxides (TCOs) and transparent oxide semiconductors (TOSs) have become necessary materials for a variety of applications in the information and energy technologies, ranging from transparent electrodes to active electronics components. Perovskite barium stannate (BaSnO 3 ), a new TCO or TOS system, is a potential platform for realizing optoelectronic devices and observing novel electronic quantum states due to its high electron mobility, excellent thermal stability, high transparency, stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
83
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 157 publications
(178 reference statements)
0
83
0
1
Order By: Relevance
“…For example, perovskite BaSnO 3 has drawn significant recent attention because of its record breaking mobility. 11 A common shortcoming of most transparent conducting oxides is that they rely on doping or alloying a wide bandgap semiconductor. This approach is limited because of possible doping bottlenecks and reduced mobility due to scattering by impurity atoms.…”
Section: Introductionmentioning
confidence: 99%
“…For example, perovskite BaSnO 3 has drawn significant recent attention because of its record breaking mobility. 11 A common shortcoming of most transparent conducting oxides is that they rely on doping or alloying a wide bandgap semiconductor. This approach is limited because of possible doping bottlenecks and reduced mobility due to scattering by impurity atoms.…”
Section: Introductionmentioning
confidence: 99%
“…BaSnO3 has three-dimensional framework of corner-sharing SnO6 octahedra, having a linear Sn-O-Sn bonding angle 180° with ideal cubic Pm3m space group [7]. By doping, with suitable dopants materials the properties of the BaSnO3 can be modified in a wide range due to its high substitutional flexibility [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, we have demonstrated that the electron transport properties of the LBSO should play not only as electron acceptors but also ionized impurities, they may increase the scattering cross section of the electrons and contribute to the mobility suppression [21][22][23] . We hope to clarify the effect of Sn valence state on the electron mobility of LBSO films in near future.…”
mentioning
confidence: 99%